Le Dhofar : de la guerre au développement - Rondot, Philippe (Le Monde diplomatique, 1984)
Keywords: Dhofar

La guérilla du Dhofar entre dans une nouvelle phase - Viennot, Jean-Pierre (Le Monde diplomatique, 1972)
Keywords: Dhofar

D'inspiration marxiste-léniniste, la guérilla du Dhofar est en lutte contre le plus archaïque des régimes - Viennot, Jean-Pierre (Le Monde diplomatique, 1970)
Keywords: Dhofar

Le sultanat d’Oman devant la rébellion du Dhofar: - Rondot, Philippe (Maghreb-Machrek, 1975)
Keywords: Dhofar

Review of Die nomaden Dhofars/Sultanat Oman. Traditionelle lebensformen in wandel - di Perna, Tiziana (Oriente Moderno, 1985)
Keywords: Dhofar; Recension

Review of From Camel to Truck: The Bedouin in the Modern World; Nomads in the Sultanate of Oman: Tradition and Development in Dhofar - Dresch, Paul (International Journal of Middle East Studies, 1989)
Keywords: Dhofar; Recension

Review of Nomads in the Sultanate of Oman: Tradition and Development in Dhofar - Eickelman, Dale F. (Middle East Journal, 1987)
Keywords: Dhofar; Recension

Review of Die Nomaden Dhofars/Sultanat Oman: Traditionelle Lebensformen Im Wandel [The nomads of Dhofar/Sultanate of Oman: changes of traditional life-styles]. Bamberger Geographische Schriften, Vol. 3 - Melamid, Alexander (Middle East Studies Association Bulletin, 1983)
Keywords: Dhofar; Recension

Explorations in Dhofar, Oman - Albright, Frank P. (Antiquity, 1955)
Keywords: Dhofar

The regionalization of the war in Oman and the fate of the tribal groups in Dhofar - 9th June Studies (The Popular Front for the Liberation of Oman, 1975)
Keywords: Dhofar; Vie politique -- Oman -- 1970-2020

Britain and Oman: The Dhofar War and its Significance - McKeown, John (University of Cambridge, 1981)
Keywords: Dhofar

Review : Plants of Dhofar. The Southern Region of Oman, Traditional Economic and Medicinal Uses - Serjeant, Robert Bertram (The Journal of the Royal Asiatic Society of Great Britain and Ireland, 1989)
Keywords: Dhofar; Recension

Review: Plants of Dhofar: The Southern Region of Oman. Traditional, Economic and Medicinal Uses - Cope, T. A. (The Geographical Journal, 1990)
Keywords: Dhofar; Recension

Victory in Hades : The Forgotten Wars of the Oman 1957-1959 and 1970-1976. Part 2: The Dhofar Campaign - Monick, S. (Scientia Militaria, 1983)
Keywords: Dhofar

Der Konflikt um Dhufar und die Aussichten auf seine Beilegung - Koszinowski, T. (Orient, 1976)
Keywords: Dhofar

Review : Nomads in the Sultanate of Oman: Tradition and Development in Dhofar By Jorg Jansen. Boulder and London: Westview Press, 1986 - Birks, J.S. (International Migration Review, 1987)
Keywords: Dhofar; Recension

Guevara Through the Looking Glass: a View of the Dhofar War - Tremayne, Penelope (The RUSI Journal, 1974)
Keywords: Dhofar

Jebel Akhdar and Dhofar: footnote to empire - Newsinger, John (Race & Class, 1998)
Keywords: Dhofar

Soviet policy towards the rebellion in Dhofar - Hensel, Howard M. (Asian Affairs, 1982)
Keywords: Dhofar

La guérilla du Dhofar - Laliberté, Gérard (Études internationales, 1973)
Keywords: Dhofar

Tribal practices, and folklore of Dhofar : Sultanate of Oman - Tabook, Salim Bakhit Salim (University of Exeter, 1997)
Keywords: Dhofar

The Jebel Akhdar war in Oman, 1954-1959 - Meagher, John B. (1985)
Keywords: Dhofar

Personal names in the regional areas of the Sultanate of Oman. Materials for the study of Arabic anthroponymy - Oman, Giovanni (Annali dell'Istituto Universitario Orientale di Napoli, 1982)
This is the third study on the Arabic anthroponomy of the Sultanate of Oman. It concerns the personal names of the telephone subscribers of 17 regional areas which form the third part of the telephone directory of the Sultanate, taken as a basis for the research. The first study dealt with the personal names of the Southern Region (Personal names in the Southern Region (Ẓufār) of the Sultanate of Oman. Oriente Moderno (Rome), vol. 60 (1980), 181-195), while the second included the names of the so called Capital Area (Cahiers d’Onomastique Arabe. Paris: CNRS, 1981). On pp. 529-530 a list of regions with the particular religious beliefs of the tribes, as far as information was available.
Keywords: Dhofar

Hadramaut, Oman, Dhufar: the experience of revolution - Kelly, J.B. (Middle Eastern Studies, 1976)
Keywords: Dhofar

Ẓufār in the Middle Ages - Guest, R. (Islamic Culture, 1935)
Keywords: Dhofar

The Dhofar District - Craufurd, C. (The Geographical Journal, 1919)
Keywords: Dhofar

Malā’ikat al-Jabal al-Akhdar. Qiṣṣat al-Thawra al-ʿUmāniyya fī Marḥalatihā al-ūlà. Bidāyat al-Marḥala al-thāniya - Ṭā’ī, ʿAbdallāh. Muḥammad al- (Maṭābiʿ al-Wafā’, 1966)
Keywords: Dhofar

Ẓufār. Qiṣṣat al-Ṣirāʿ al-Siyāsī wa’l-ʿAskarī fī ‘l-Khalīj al-ʿArabī, 1970-1976 - Rayyis, Riyāḍ Najīb al- (Portico, 1978)
Keywords: Dhofar

News from Oman and Southern Arabia - KROAG (The Committee for the Revolution in Oman and the Arabian Gulf) (9th June Publishers, 1981)
Keywords: Dhofar

News from Oman (Dhofar Letter) - KROAG (The Committee for the Revolution in Oman and the Arabian Gulf) (9th June Publishers, 1979)
Keywords: Dhofar

Die moderne Entwicklung im nomadisch-bauerlichen Lebensraum der südomanischen Region Dhofar - Janzen, Jörg (Beduinen im Zeichen des Erdöls: Studien zur Entwicklung im beduinischen Lebensraum Südost-Arabiens, 1981)
Keywords: Dhofar

Erste Ergebnisse und Tendenzen des jungen Wandels in der Lebens- und Wirtschaftsweise der Nomaden Dhofars/Sultanat Oman - Scholz, Fred (Nomadismus - ein Entwicklungsproblem?, 1982)
Keywords: Dhofar

La guérilla au Dhofar ou le mouvement de libération dans le Golfe arabe - Laliberté, Gérard (Université Paris 1, 1971)
La guérilla du FLD contre le sultan d'Oman, soutenue par le Yémen du Sud, est abordée dans un contexte historique. L'auteur analyse l'attitude du monde arabe à l'égard de la révolution dhofarie (marxisme, rapports sociaux, libération de la femme, lutte contre le tribalisme).
Keywords: Dhofar

Dhofar: the achilles heel - Wakebridge, Charles (Middle East International, 1974)
Keywords: Dhofar

The Oman war 1957-1959. A critical history - Gulf committee (Gulf committee, 1974)
Keywords: Dhofar

Front Populaire de Libération du Golfe Arabique Occupé 1965-1970 (1970)
Keywords: Dhofar

Who dares wins. The story of the Special Air Service 1950-1980 - Geraghty, Tony (Fontana, 1981)
Keywords: Dhofar

The architecture of Ṣalālah and the Dhofar littoral - Costa, Paolo M.; Kite, Stephen (Journal of Oman Studies, 1985)
Keywords: Architecture -- Oman; Dhofar

SAS: Operation Oman - Jeapes, Tony (William Kimber, 1980)
Keywords: Dhofar

Nomads in the Sultanate of Oman: tradition and development in Dhofar - Janzen, Jörg (Westview Press, 1986)
Keywords: Dhofar

Die Nomaden Dhofars/Sultanat Oman: traditionelle Lebensformen im Wandel - Janzen, Jörg (Universität Bamberg, 1980)
Keywords: Dhofar

Dhofar. What made it different? - Morris, Miranda (Oman: economic, social, and strategic developments, 1987)
Keywords: Dhofar

The Secret War: Dhofar 1971-1972 - Arkless, David C. (William Kimber, 1988)
Keywords: Dhofar

A St. George of Dhofar - Johnstone, Thomas Muir (Arabian Studies, 1978)
Keywords: Dhofar